2017
DOI: 10.1111/bld.12195
|View full text |Cite
|
Sign up to set email alerts
|

“…their opinions mean something”: Care staff's attitudes to health research involving people with intellectual disabilities

Abstract: Accessible summary• It is important for people with intellectual disabilities to be involved in research about their health care.• Eight people working in the care sector were interviewed about their views about supporting people with intellectual disabilities to take part in research.• Care staff were positive about research but talked about things that may make it difficult for people with intellectual disabilities to take part in research.• We suggest some ideas that could help care staff and researchers to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 24 publications
(41 reference statements)
0
17
0
Order By: Relevance
“…Ensuring reciprocity, by providing feedback from researchers to participants, is important (Lewis and Porter, 2004;Phillipson et al, 2012). Hall et al (2017) found supportive managers to be the key to successful recruitment, reporting on the difficulty for staff to engage with research when unsupported by senior management. They found that senior managers' perception on the importance of research greatly determined how much time and resource were allocated, subsequently affecting whether or not staff would be able to participate at all in research.…”
Section: Discussionmentioning
confidence: 99%
“…Ensuring reciprocity, by providing feedback from researchers to participants, is important (Lewis and Porter, 2004;Phillipson et al, 2012). Hall et al (2017) found supportive managers to be the key to successful recruitment, reporting on the difficulty for staff to engage with research when unsupported by senior management. They found that senior managers' perception on the importance of research greatly determined how much time and resource were allocated, subsequently affecting whether or not staff would be able to participate at all in research.…”
Section: Discussionmentioning
confidence: 99%
“…This is a complex situation, however, and research has recently emerged (McDonald et al, 2017) that suggests that people with intellectual disabilities and other stakeholders agree that 'someone else' making the research participation decision, hindering research access, is harmful. Hall et al (2017) recommend contacting gatekeepers well in advance to explain the study and answer questions, making clear to them that the process and interview guide can be adapted as needed.…”
Section: Accessmentioning
confidence: 99%
“…This encouraged a more engaging conversation than a structured interview which allowed the YADD to be fully comfortable in jumping in and out of questions by providing his in-depth perspective/ thoughts on matters. (Field log notes P68) As the paragraph above shows, our team implemented some suggestions also recommended by other researchers, to better adapt the interview to individuals with DDs including asking questions in an informal manner, rephrasing them, and having short sessions (Hall et al, 2017).…”
Section: Strategies To Accommodate Yaddmentioning
confidence: 99%
“…Although people with disabilities experiences socioeconomic and health inequities, they are underrepresented in research that aims at proposing policy recommendations and practices to promote equal opportunities and inclusion (Hall, Durand, & Mengoni, 2017). Buettgen et al (2012) state that “there is a link between the way that research in the developmental area has been conducted and the disenfranchisement of developmentally disabled people” (p. 604).…”
Section: Dds: Interlocking Exclusionsmentioning
confidence: 99%